Developing Mekarsari Gambung Village as an Integrated Educational Tourism Area : Perencanaan Desa Mekarsari Gambung Sebagai Kawasan Eduwisata Terpadu - Chandra Budhi Septyandi; Syifaa Novianti; Sherly Raka Siwi Putri Utomo; Marceilla Suryana; Dinarsiah Chendraningrum (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Community-based tourism development is one of the effective strategies to increase the economic potential and welfare of local communities. As a model for tourism development, tourist villages prioritize cultural values, local wisdom, and environmental sustainability by actively involving the local community in tourism activities. This concept aims to promote sustainable and inclusive tourism, where local communities directly benefit through the provision of tourism services and products, such as homestays, handicrafts, traditional cuisine, and cultural attractions. Mekarsari Gambung, as one of the tourist villages developed through the Bandung State Polytechnic's Fostered Village program, exemplifies how tourism management can be carried out using a community-based approach. In its development, educational tourism packages like EduTea, EduCoffee, and Dairy Farm Half Day Trip are designed not only to provide tourism experiences for visitors but also to strengthen the skills and knowledge of local communities. Community involvement in these tourism activities can open up new job opportunities, increase income, and encourage the preservation of village culture and environment. The fostered village program also supports the development of human resource capacity through training and mentoring, ensuring the continuous improvement of tourism service quality. Thus, the development of sustainable and community-based tourism tourist villages provides long-term benefits for village development and community welfare.